Tumor-Cell Co-Culture Induced Alternative Activation of Macrophages Is Modulated by Interferons In Vitro - Müller-Quernheim, Ulrike Carolin (Mary Ann Liebert, Inc., 2012)
Tumor-associated macrophages infiltrate tumors and facilitate tumor growth. Here, we analyzed M1 and M2 marker expression in the course of co-culture-driven macrophage differentiation and investigated the influence of interferons (IFNs) on this differentiation. To generate monocyte-derived macrophages (MDMs) 1×10(6) monocytes of healthy volunteers were cultivated either with 25×10(3) adherent A549/mL or in medium containing 50% A549 conditioned medium (CM) for 72 h in the presence or absence of IFN-α, β or γ, respectively. Supernatants were tested for CCL18 (M2 marker) and CXCL10 (M1 marker) by enzyme-linked immunosorbent assay. CCL18 and CXCL10 release by MDM is increased by the presence of A549 cells, but also when cultured in A549 CM. On stimulation with IFN-γ, we observe an increased release of the M1 marker CXCL10 and a decreased release of CCL18. Type I IFNs also increases CXCL10 release. Thus, A549 releases a soluble factor which enhances CCL18 production and M2 polarization, indicating that a localized specific cytokine milieu, as found in the environment of a tumor or in fibrotic lung tissue, favors alternative activation of macrophages. In the presence of IFN-γ, M2 differentiation is attenuated as shown by the decrease of the M2 chemokine CCL18 and by the increase of the M1 chemokine CXCL10. However, CXCL10 levels were also increased by the co-culture, which indicates a simultaneous classical activation (M1) or the formation of a M1/M2 hybrid.